INOVASI PENGEMBANGAN WISATA KAMPUNG NELAYAN DI KECAMATAN ENDE SELATAN, KABUPATEN ENDEURAHAN TETANDARA, RUKUN LIMA, DAN PAUPANDA, KECAMATAN ENDE SELATAN, KABUPATEN ENDE - Sugiyanto, Sugiyanto; Yunanto, Mohammad Kus; Yulianto, Daris (Universitas Medan Area, 2020)
The tourism sector is considered as a stimulant of regional economic activity. However, innovative strategies are needed in developing existing local potential. The purpose of this research is to contribute ideas in solving the problem of the lack of community welfare in Tetandara Village, Rukun Lima, Paupanda. Some of the problems include: limited infrastructure to support tourism, poor quality of human resources, poverty, and the majority of the population living in slums. This research uses a qualitative method with a case study approach. The source of the data obtained through interviews and Focus Group Discussions. Based on the results of research in three study locations the need for tourism development while still paying attention to aspects of attraction, accessibility, convenience, and ancillary. The three study locations have similarities in terms of geography and the main economic activities that are in the coastal area and fishermen are the dominant livelihoods. On the one hand, the main problem lies in poverty with minimal income. The concept of development innovation is fishing village tourism that not only looks at physical development but also pays attention to its non-physical aspects, such as local institutions that are closely related to human resources. Required the formation of Pokdarwis institutions that must work together with cooperatives and BUMDesa as a form of support for the sustainability of tourism